Economic implications of COVID-19 for the HIV epidemic and the response in Zimbabwe. Issue 4 (2nd October 2022) - Birungi, Charles; Haacker, Markus; Taramusi, Isaac; Mpofu, Amon; Madzima, Bernard; Apollo, Tsitsi; Mugurungi, Owen; Odiit, Martin; Obst, Michael A
Abstract : Understanding the economic implications of COVID-19 for the HIV epidemic and response is critical for designing policies and strategies to effectively sustain past gains and accelerate progress to end these colliding pandemics. While considerable cross-national empirical evidence exists at the global level, there is a paucity of such deep-dive evidence at national level. This article addresses this gap. While Zimbabwe experienced fewer COVID-19 cases and deaths than most countries, the pandemic has had profound economic effects, reducing gross domestic product by nearly 7% in 2020. This exacerbates the long-term economic crisis that began in 1998. This has left many households vulnerable to the economic fallout from COVID-19, with the number of the extreme poor having increased to 49% of the population in 2020 (up from 38% in 2019). The national HIV response, largely financed externally, has been one of the few bright spots. Overall, macro-economic and social conditions heavily affected the capacity of Zimbabwe to respond to COVID-19. Few options were available for borrowing the needed sums of money. National outlays for COVID-19 mitigation and vaccination amounted to 2% of GDP, with one-third funded by external donors. Service delivery innovations helped sustain access to HIV treatment during national lockdowns. As a result of reduced access to HIV testing, the number of people initiating HIV treatment declined. In the short term, there are likely to be few immediate health care consequences of the slowdown in treatment initiation due to the country's already high level of HIV treatment coverage. However, a longer-lasting slowdown could impede national progress towards ending HIV and AIDS. The findings suggest a need to finance the global commons, specifically recognising that investing in health care is investing in economic recovery.